Oxidation resistant flexible transparent conductive electrodes by synthesising CuNi nanowires. - Krause, Philip George (Cranfield University, 2018)
This research attempts to find a replacement for ITO that is flexible and doesn’t oxidise by synthesising CuNi nanowires in a single pot process. Indium is scarce, expensive, and non-flexible so has to be printed on solid substrates such as glass. It involved costly and wasteful processes to apply and cure and is running out. Copper nanowires are a cheap alternative but they oxidise. The simple difference between synthesising Cu NW’s and CuNi NW’s is the addition of glucose which is low cost. The nickel inhibits oxidation so no extra processes are required to protect them. Copper-nickel nanowires have rarely been synthesised and this research explains how to and shows that copper-nickel nanowires could directly replace ITO. This research shows a systematic approach to solving the problem, by varying the glucose and heat cycle to maximise the aspect ratio and achieve a nickel content of 5 > 20%. Once the best nanowires were synthesised, the ink concentration and thickness was varied to optimise the optoelectronic properties. Many CuNi NW’s were grown with >700 aspect ratio and Ni content 5 > 20% by adjusting the glucose content. The aspect ratio increases when the synthesis temperature is lowered as low as 160 °C while maintaining the Ni content range. A compromise is necessary as higher nickel content reduces the aspect ratio. A synthesis of 8.9% Ni was found to be as conductive after 112 days, as it was when it was made, thus showing that CuNi alloy does inhibit oxidation. This research has shown that CuNi NW’s can replace ITO in every area while being over 100 times less expensive and easier to make, apply and cure, enabling more uses of this technology in the future. They are also flexible which will allow even more areas of use.
Keywords: ITO replacement; copper nickel nanowires; low temperature synthesis; one pot synthesis; flexible; glucose